Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika Berdasarkan Prosedur Newman: Analysis of Student Errors in Solving Math Story Problems Based on Newman's Procedure - asni Afriandani; Wahyuddin; Nursakiah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
The main purpose of this study is to describe the errors and causes of student errors in solving math story problems with a two-variable linear equation system based on the Newman procedure. This type of research is a descriptive study with a qualitative approach which was carried out at SMP Negeri 3 Salomekko. The subjects of this study consisted of 3 people who were taken each 1 student with low ability, medium ability and high ability. Data collection techniques used test and interview methods, and instrument validation was carried out with 2 expert validation stages. Technical data analysis using descriptive analysis and qualitative data analysis starting from data reduction, data presentation and drawing conclusions. From the results of the study, it was concluded that high-ability subjects made misunderstandings and errors in writing the final answer. Subjects who are capable of making transformation errors, process skill errors and writing errors in the final answer. Low-ability subjects made reading errors, understanding errors, transformation errors, process skills errors and writing errors in the final answer. The causes of student errors are 1) reading errors are caused by haste and confusion in interpreting the meaning of the word. 2) misunderstandings are caused by lack of knowledge in interpreting the meaning of words and forgetting. 3) the transformation error is caused by not understanding the problem and being confused about working on the problem. 4) process skill errors are caused by lack of thoroughness and haste. 5) the error in writing the final answer is caused by lack of thoroughness, haste, and did not find the final result. Keyword: Student errors, Solving math story problems, Newman procedure